Mitotically active cellular fibroma of the ovary: a case report and literature review. Issue 1 (December 2015) - Yamada, Takashi; Hattori, Kimiaki; Satomi, Hidetoshi; Hirose, Yoshinobu; Nakai, Go; Daimon, Atsushi; Hayashi, Atsushi; Terai, Yoshito; Ohmichi, Masahide; Fukunaga, Masaharu
Abstract Background The ovarian cellular fibrous tumor with mitotic figure >4 per 10 high power field without moderate to severe atypia is defined as mitotically active cellular fibroma according to the 2014 World Health Organization classification. As this category is new and rare now, we described here a case of MACF and reviewed the literature. Case We present a case of mitotically active cellular fibroma of the ovary with 10-year history that was treated with laparoscopic surgery. Methods We reviewed the relevant literature using PubMed search system and analyzed the previous cases. Results To date, only 5 cases of mitotically active cellular fibroma have been reported. Our patient is the first case of mitotically active cellular fibroma of the ovary treated with laparoscopic surgery. Conclusion MACF of the ovary is a newly defined category and few cases have been reported, while prognostic factors have also not yet been fully characterized. Long-term clinical follow-up is necessary.